Olmesartan improves pulse wave velocity and lowers central systolic blood pressure and ambulatory blood pressure in patients with metabolic syndrome - Raff, Ulrike; Walker, Stefanie Elke; Ott, Christian; Schneider, Markus P.; Schmieder, Roland (Journal of Clinical Hypertension, 2015)
Ambulatory blood pressure (BP) and central systolic BP (cSBP) are superior to brachial office BP measurements in predicting cardiovascular end organ damage. The authors aimed to analyze the effect of olmesartan 80 mg (OLM 80) vs 20 mg (OLM 20) vs amlodipine 5 mg (AML 5) on central hemodymamics and ambulatory BP in patients with metabolic syndrome (MetS).In a double-blind, three-phase crossover study comprising 69 untreated patients with MetS defined by the Third Report of the Expert Panel on Detection, Evaluation, and Treatment of High Blood Cholesterol in Adults guidelines, the effects of OLM 80 on central hemodynamics (cSBP), central pulse pressure), pulse wave velocity (PWV), and 24-hour ambulatory BP were compared with OLM 20 and AML 5, given for 6 weeks each. In 69 patients (47 men, 22 women) (51.5±9.75 years), reduction in cSBP was the highest with OLM 80 and significantly greater than the reduction with AML 5 (-14.1 mm Hg vs -9.7 mm Hg, P=.0117). All three substances significantly reduced 24-hour ambulatory systolic (OLM 80 and OLM 20 P<.0001; AML 5 P=.0105). BP and 24-hour diastolic BP (OLM 80 and OLM 20 P<.0001; AML 5 P=.0126). PWV was significantly reduced by OLM 80 (-0.58 m/s, P=.0088) and by OLM 20 (-0.48 m/s, P=.0362) but not by AML 5 (-0.28 m/s, P=.2065). For PWV, no significant differences were detected between the three groups. OLM significantly improves arterial stiffness as demonstrated by the reduction in PWV and in cSBP. In addition, 24-hour ambulatory BP was reduced to a greater extent with OLM 80 than with AML 5.
EVALuna2:3748

Plasma histamine and tumour necrosis factor-alpha levels in Crohn's disease and ulcerative colitis at various stages of disease - Hagel, Alexander; De Rossi, T.; Konturek, Peter; Albrecht, H.; Walker, Stefanie Elke; Hahn, Eckhart Georg; Raithel, M. (Journal of Physiology and Pharmacology, 2015)
Mast cells secrete numerous mediators and this study investigated plasma levels of histamine, and tumor necrosis factor alpha (TNF-?) in chronic inflammatory bowel disease (IBD). Plasma levels of histamine were determined in 68 patients with Crohn's disease (CD), 22 with ulcerative colitis (UC) and 13 controls. TNF-? levels were assessed in 29 CD patients, 11 UC patients, and in 11 controls. Plasma histamine levels in the control group were 0.25 ng (0.14 - 0.33) and showed no difference to CD (0.19 ng, 0.09 - 0.35) or UC (0.23 ng, 0.11 - 0.60). Significantly lower histamine levels were only found in CD patients on 5-aminosalicylic acid treatment (P <= 0.04). Plasma TNF-? levels in the control group were significantly lower 0.44 ml/m(2) (0 - 1.15) than in CD patients (4.62 ml/m(2), 1.82 - 9.22, P = 0.005) or UC (3.14 ml/m(2); 0.08 - 11.34, P = 0.01). In CD disease activity, fistula, and extraintestinal manifestations (EM) were associated with significantly higher plasma TNF-? values, but not the type of treatment. We concluded that in contrast to TNF-?, histamine levels were normal in CD and UC. There is no correlation with histamine and thus the proportion of TNF-? secreted from mast cells in the plasma in patients with IBD is less important.
EVALuna2:2032